Magnesium-based metasurfaces for dual-function switching between dynamic holography and dynamic color display - Li, Jianxiong; Chen, Yiqin; Hu, Yueqiang; Duan, Huigao; Liu, Na (ACS nano, 2020)
Metasurface-based color display and holography have greatly advanced the state of the art display technologies. To further enrich the metasurface functionalities, recently a lot of research endeavors have been made to combine these two display functions within a single device. However, so far such metasurfaces have remained static and lack tunability once the devices are fabricated. In this work, we demonstrate a dynamic dual-function metasurface device at visible frequencies. It allows for switching between dynamic holography and dynamic color display, taking advantage of the reversible phase transition of magnesium through hydrogenation and dehydrogenation. Spatially arranged stepwise nanocavity pixels are employed to accurately control the amplitude and phase of light, enabling the generation of high-quality color prints and holograms. Our work represents a paradigm toward compact and multifunctional optical elements for future display technologies.